Women$1 (Bs Health in Interventional Radiologys - Ignacio, Elizabeth; Venbrux, Anthony C.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Written as a concise, clinical guide to major interventional procedures impacting upon women$1 (Bs health, Women$1 (Bs Health in Interventional Radiology focuses on a wide range of vascular and non-vascular interventions commonly performed in daily practice, including those related to the pelvis, fallopian tube, spine, and lower extremities. Chapters provide key clinical background information on each intervention, including pathophysiology, clinical manifestations, basic anatomy, and imaging features, before moving on to step-by-step explanations of the techniques. Accompanied by high-quality illustrations and images throughout, chapters also include technical hints, pearls, and pitfalls, postoperative care guidelines, outcomes data, and complications. Written by an expert group of experienced interventionalists, this book promises the reader a comprehensive overview of interventions currently performed to treat problems affecting the health of women and is a valuable resource for both practicing physicians and those in training.s
Keywords: Medicine; Radiology, Medical; Interventional radiology; Medicine & Public Health; Interventional Radiology; Imaging / Radiology